Search for plants with insecticidal properties for Sitophilus zeamais control in stored corn - Silva, Gonzalo; Orrego, Odette; Hepp, Ruperto; Tapia, Maritza (Pesquisa Agropecuaria Brasileira, 2005)
Twenty three powdered plants were evaluated under laboratory conditions against Sitophilus zeamais Mots. on stored corn. In the first part of the work all plants were evaluated at a concentration of 1.0% (w/w). Furthermore the powders with best results were evaluated at concentrations of 0.1, 0.5, 1.0 and 2.0% on corn grains infested with insects during 24 hours, 30, 60 and 90 days. Sixty three treatments in a completely randomized experimental design were evaluated and the study was replicated three times. In the first stage the highest level of insect mortality was exhibited with Chenopodium ambrosioides L. and Peumus boldus Mol. at 1.0% concentration (w/w), with values of 65.8% and 99.3%, respectively. The highest insect emergence reductions were obtained with the same treatments and the grain weight was reduced up to 13.0%. In the evaluation with more concentrations, the best results were obtained with treatments at 1.0% and 2.0% (w/w), with C. ambrosioides the insect mortality values were 90.3% and 90.1% and with P. boldus mortalities of 97.1% and 98.8% were achieved. The residual effect lasted up to 24 hours.